DIRECTION OF EDUCATIONAL POLICY IN THE FORMATION OF TEACHER PROFESSIONALISM IN THE SUBJECT OF CIVIC AND CITIZENSHIP EDUCATION IN AUSTRALIA - Kusuma, Wahyu Jati; Samidi, R.; Purbasari, Verbena Ayuningsih (Journal of Social Politics and Governance (JSPG), 2025)
This paper discusses the direction of educational policy in the formation of teacher professionalism in the subject of Civic and Citizenship Education (CCE) in Australia by reviewing teacher qualification standards, learning strategies, and the implementation of citizenship pedagogy in minimal–maximal contexts. This study uses a literature review method through the analysis of policy documents, scientific publications, and institutional reports related to the development of teacher professionalism. The results of the study indicate that teacher professionalism in Australia is built through comprehensive AITSL standards that emphasize professional knowledge, professional practice, and professional engagement. Teachers act as facilitators who encourage student autonomy, democratic learning, and participation in school and community environments through classroom, extracurricular, and community-based approaches. When compared with practices in Hong Kong, Australian teacher professionalism is more inclined toward the maximal context because CCE learning is directed at creating active citizens who are critical, participatory, and sensitive to contemporary socio-political issues. These findings confirm that Australian government policies make a significant contribution to strengthening teacher professionalism and the effectiveness of Civic and Citizenship Education learning.